Severe Clostridial Pyomyoma following an Abortion Does Not Always Require Surgical Intervention - Daphna Stroumsa; Eliel Ben-David; Nurith Hiller; Drorith Hochner-Celnikier (Case Reports in Obstetrics and Gynecology)
Background. Clostridial infection following pregnancy may be fatal, and surgery is considered as the treatment of choice. We suggest a conservative management in selected cases when preservation of fertility is of major importance. Case. A 41-year-old primigravida presented with abdominal pain and fever, one day following dilatation and curettage at 20 weeks of gestation. Her abdomen was diffusely tender, with a uterus enlarged to 20 weeks' gestation. Laboratory studies were consistent with sepsis and hemolysis. CT demonstrated a gas-containing mass compressing the uterine cavity, and presence of air in pelvic veins. Blood cultures were positive for Clostridium perfringens. The patient was treated conservatively, with IV antibiotics and fluid resuscitation, and recovered. Conclusion. In selected cases of infected myoma complicated by clostridial sepsis, refraining from surgical intervention is a possible therapeutic approach.